Structural, magnetic and electronic structure properties of Co doped ZnO nanoparticles - Kumar, Shalendra; Song, T. K.; Gautam, Sanjeev; Chae, K. H.; Kim, S. S.; Jang, K. W. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
We reported structural, magnetic and electronic structure studies of Co doped ZnO nanoparticles. Doping of Co ions in ZnO host matrix has been studied and confirmed using various methods; such as X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersed X-ray (EDX), high resolution transmission electron microscopy (HR-TEM), Fourier transform infrared spectroscopy (FT-IR), near edge X-ray absorption fine structure (NEXAFS) spectroscopy, magnetic hysteresis loop measurements and X-ray magnetic circular dichroism (XMCD). From the XRD and HR-TEM results, it is observed that Co doped ZnO nanoparticles have single phase nature with wurtzite structure and exclude the possibility of secondary phase formation. FE-SEM and TEM micrographs show that pure and Co doped nanoparticles are nearly spherical in shape. O K edge NEXAFS spectra indicate that 0 vacancies increase with Co doping. The Co L-3,L-2 edge NEXAFS spectra revealed that Co ions are in 2+ valence state. DC magnetization hysteresis loops and XMCD results clearly showed the intrinsic origin of temperature ferromagnetism in Co doped ZnO nanoparticles. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: ROOM-TEMPERATURE FERROMAGNETISM; MN; ZN1-XMNXO